CLINICAL EFFICACY OF MINIMALLY INVASIVE INTERVENTIONS IN THE TREATMENT OF BILITY PERITONITIS AS A COMPLICATION OF OPERATIONS FOR CHOLELITHIASIS - Halima Ikramdjanovna, Kariyeva (PT. Antis International Publisher, 2025)
Objective: This study analyzed 49 cases of bile peritonitis caused by bile leakage after bile duct surgeries, aiming to identify causative factors and assess the effectiveness of various treatments. Postoperative bile peritonitis incidence was found to be 0.8%, with